Motif-motif Penyembuhan: Interpretasi 1 Samuel 16:14-23 sebagai Terapi Musik - Tuasela, Juliana Agusthina (Asosiasi Teolog Indonesia, 2024)
This article delves into the unique role of music as a therapeutic tool in ancient Israel, with a focus on the biblical account of music therapy healing Saul (1 Samuel 16:14-23). This study attempts to explore and question the relationship between music, healing, and religion. This study aims to: first, to interpret the text of 1 Samuel 16:14-23 which introduces the significance of music in the ancient Israelite tradition. Second, to emphasizes the function of music as healing therapy, where David uses the lyre to heal Saul. This text subtly demonstrates the prevalence of the healing practice of music in the biblical world. Third, it investigates narrative interpretive methods that discuss the extent to which Israel, through David, defines himself and how the superiority of music helps shape Israel’s self-perception as a musical community. Data was collected through literature studies/scientific literature related to the title of this study. The results of the data collection will then be processed and presented in the form of a description.